Fatty acid profile of cooked leg meat and raw hepatopancreas of red king crab (Paralithodes camtschaticus) during three-month live holding without feeding at 5 and 10 °C - Lian, Federico; Siikavuopio, Sten Ivar; Harrison, Sabine M.; Vang, Birthe; Brunton, Nigel P.; Esaiassen, Margrethe; Lorentzen, Grete Elisabeth (Journal of Food Composition and Analysis, 2022)
The red king crab (RKC, Paralithodes camtschaticus) is a highly-valued decapod species. Typically, RKCs undergo a period of live holding (LH), often without feeding, in onshore facilities, allowing for flexible management before export to destination markets. This study aimed to (i) gain information on the fatty acid (FA) profile of the cooked leg meat and raw hepatopancreas obtained from RKC harvested in Norwegian waters of the Barents Sea and (ii) investigate how these FA profiles are affected by LH without feeding for up to 92 days at 5 or 10 °C. Minor changes were observed in the FA profile of cooked leg meat, which retained its nutritional value in omega−3 FA content. In contrast, the FA composition of raw hepatopancreas was severely affected by the LH time, with substantial changes occurring especially between 41 and 62 days at 10 °C and between 62 and 92 days at 5 °C. Saturated and specific monounsaturated FAs (16:1n−7c and 18:1n−9t), as well as 22:5n−3c, were preferentially utilized at the beginning of the starvation period, followed by the mobilization of C18–22 unsaturated FAs. Long-chain highly-unsaturated FAs were preferentially retained during LH, especially 20:4n−6c and 20:5n−3c. The information emerging from the present study may be practically exploited for selecting or designing suitable feed for RKC during LH at different temperatures.